Thrombectomy Complications in Large Vessel Occlusions: Incidence, Predictors, and Clinical Impact in the ETIS Registry. Issue 12 (December 2021) - Happi Ngankou, Emmanuel; Gory, Benjamin; Marnat, Gaultier; Richard, Sébastien; Bourcier, Romain; Sibon, Igor; Dargazanli, Cyril; Arquizan, Caroline; Maïer, Benjamin; Blanc, Raphaël; Lapergue, Bertrand; Consoli, Arturo; et al.
Abstract : Background and Purpose: Procedural complications in thrombectomy for large vessel occlusions of the anterior circulation are not well described. We investigated the incidence, risk factors, and clinical implications of thrombectomy complications in daily clinical practice. Methods: We used data from the ongoing prospective multicenter observational Endovascular Treatment in Ischemic Stroke Registry in France. The present study is a retrospective analysis of 4029 stroke patients with anterior large vessel occlusions treated with thrombectomy between January 2015 and May 2020 in 18 centers. We systematically collected procedural data, incidence of embolic complications, perforations and dissections, clinical outcome at 90 days, and hemorrhagic complications. Results: Procedural complications occurred in 7.99% (95% CI, 7.17%–8.87%), and embolus to a new territory (ENT) was the most frequent (5.2%). Predictors of ENTs were terminal carotid/tandem occlusion (odds ratio [OR], 5 [95% CI, 2.03–12.31]; P <0.001) and an increased total number of passes (OR, 1.22 [95% CI, 1.05–1.41]; P =0.006). ENTs were associated to worse clinical outcomes (90-day modified Rankin Scale score, 0–2; adjusted OR, 0.4 [95% CI, 0.25–0.63]; P <0.001), increased mortality (adjusted OR, 1.74 [95% CI, 1.2–2.53]; P <0.001), and symptomatic intracerebral hemorrhage (adjusted OR, 1.87 [95% CI, 1.15–3.03]; P =0.011). Perforations occurred in 1.69% (95% CI, 1.31%–2.13%). Predictors of perforations were terminal carotid/tandem occlusions (39.7% versus 27.6%; P =0.028). 40.7% of patients died at 90 days, and the overall rate of poor outcome was 74.6% in case of perforation. Dissections occurred in 1.46% (95% CI, 1.11%–1.88%) and were more common in younger patients (median age, 64.2 versus 70.2 years; P =0.002). Dissections did not affect the clinical outcome at 90 days. Besides dissection, complications were independent of the thrombectomy technique. Conclusions: Thrombectomy complication rate is not negligible, and ENTs were the most frequent. ENTs and perforations were associated with disability and mortality, and terminal carotid/tandem occlusions were a risk factor. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03776877. Abstract : Supplemental Digital Content is available in the text.